Differential impact of educational attainment on later life cognition by race/ethnicity in the Project Talent Aging Study. (31st December 2021) - Thomas, Marilyn D; Calmasini, Camilla; Seblova, Dominika; Manly, Jennifer J; Lapham, Susan; Peters, Kelly; Prescott, Carol Arlene; Mangurian, Christina; Glymour, M Maria
Abstract: Background: Increased education reduces risk of late life cognitive impairment. However, racial/ethnic inequities in cognitive outcomes persist at all levels of education. These findings suggest the need to evaluate whether race/ethnicity modifies the association between education and cognition overall and within specific cognitive domains. Method: Data are from 2, 078 participants of Project Talent Aging Study, a nationally representative study of high school students sampled in 1960 and followed up for cognitive assessments at the average age of 75 years. Three cognitive domains were selected, z‐scored, and evaluated separately and as a composite measure: verbal fluency, memory/recall, and attention. We used multivariable linear regression to estimate main associations between years of education and cognitive outcomes, and then evaluated statistical interaction with race/ethnicity. All models were adjusted for age, childhood socioeconomic status, childhood self‐reported health status, number of school absences, and adolescent cognitive ability. Result: The sample included White (81.4%), Black (9.2%), and Other race/ethnicities (9.4%). Each additional year of education was associated with higher scores on the cognitive composite measure (β=0.053; 95% confidence interval [CI]=0.031, 0.076). In the cognitive composite model with interactions, the estimate for White respondents was β=0.048 (95% CI=0.024, 0.071) and the interaction with education for Black respondents was β=0.019 (CI=‐0.062, 0.099). Within cognitive domains, each additional year of education was associated with better verbal fluency (β=0.058; 95% CI=0.035, 0.081) and attention (β=0.040; 95% CI=0.017, 0.063), but not recall (β=0.014; 95% CI=‐0.011, 0.038). Among cognitive domain‐specific models with interactions, the attention domain estimate was significantly different for Black compared to White respondents: the estimate for White adults was β=0.030 (CI=0.005, 0.055) and the interaction with education for Black adults was β=0.106 (CI=0.022, 0.189). Conclusion: Greater educational attainment predicted better overall cognition, verbal fluency, and attention for US adults. Associations for verbal fluency and memory were similar for racial groups; however, education offered an additional benefit for Black adults in the attention domain compared to White adults later in life. Future research should explore whether educational opportunities and quality may have differential cognitive implications across racial/ethnic groups.